Perceptions and suggestions of second year medical professional students of deemed health university about their teaching and learning process in pharmacology: an analytical study - Bhat, Nagapati Prabhakar; Rao, SN (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The teaching learning process in 2nd year medical professional course is crucial. Learning in the 2nd year medical students acts as a foundation on which a process of becoming a good professional is resting. Pharmacology is a medical science that forms a backbone of the medical profession as drugs form the corner stone of therapy in human diseases. So, in order to assess the strength of the pharmacology curriculum and students’ learning experience, collection of the students’ feedback is important so that necessary reforms can be implemented for the betterment of teaching/learning of the subject. Objective of this questionnaire based study was conducted to determine the perceptions of 2nd year medical professional students about various aspects of their teaching and learning, in order to make teaching more effective and enable students to learn better. Methods: This was a questionnaire based analytical study. The first part of the questionnaire contains respondent’s general information. The second part of the questionnaire was in multiple choices format with a space for suggestions/remarks. The response was reviewed and analysis was done. Results: Out of total 180 students, 111 were able to complete the survey. Out of them 2 were not filled the first part of the questionnaire (respondent’s general information). Out of 109 duly filled questionnaires 43 were males and 66 females and the mean age of the students was 20 years. Majority of the students found Pharmacology to be the most relevant and useful subject in further profession and future. About teaching learning media in understanding the subject in theory class majority of students preferred combination of chalk and board as well as power point presentation (PPT). Regarding the reforms to be made in the curriculum, majority of the students opined that group discussions should be introduced. Regarding preparation for annual university exams most of students felt class tests were useful. Conclusions: This study has helped us in knowing the student preferences regarding pharmacology teaching and its outcomes would be helpful in modifying undergraduate pharmacology teaching pattern.